Association Between Obesity and Global Longitudinal Strain: A Cross-Sectional Study in a University Hospital in Iran - Sadeghi, Soheila; Omidi, Fatemeh (Novelty in Biomedicine, 2024)
Background: Obesity is a prevalent health issue associated with an increased risk of cardiovascular diseases. While obesity's link to various cardiovascular conditions is well-documented, its specific impact on global longitudinal strain (GLS) requires further investigation. This study aims to explore the relationship between obesity and GLS in an adult population. Materials and Methods: This cross-sectional study included 91 adult participants, categorized into obese (n=59) and non-obese (n=32) groups based on body mass index (BMI). GLS was measured using speckle-tracking echocardiography. Chi-square tests and odds ratios (OR) were used to assess the association between obesity and abnormal GLS. Results: Among the non-obese group, 25.0% had abnormal GLS compared to 20.3% in the obese group. The chi-square test indicated no significant difference in the prevalence of abnormal GLS between the groups (p = 0.60). The odds ratio for abnormal GLS in obese versus non-obese participants was 1.3 (95% CI: 0.4-3.6), indicating no significant association. Conclusion: The study found no significant association between obesity and abnormal GLS, suggesting that BMI alone may not be a reliable predictor of subclinical myocardial dysfunction. These findings highlight the need for a comprehensive approach to cardiovascular risk assessment that includes multiple factors beyond BMI.